Household Leverage and the Recession - Jones, Callum (IMF Working Papers; Working Paper, 2018)
We evaluate and partially challenge the 'household leverage' view of the Great Recession. In the data, employment and consumption declined more in states where household debt declined more. We study a model where liquidity constraints amplify the response of consumption and employment to changes in debt. We estimate the model with Bayesian methods combining state and aggregate data. Changes in household credit limits explain 40 percent of the differential rise and fall of employment across states, but a small fraction of the aggregate employment decline in 2008-2010. Nevertheless, since household deleveraging was gradual, credit shocks greatly slowed the recovery.